The Sounds and Sound Symbols of the Pangasinan Language - Viray, Felizberto B. (The Archive; Vol 5 (1926): Paper No. 5: The Sounds and Sound Symbols of the Pangasinan Language, 2024)
In the present paper I wish to present, in the first place, the results of a study made by me of the sound system of my mother language which is spoken in a province of Luzon bordering on the Gulf of Lingayen, and is called after that province the Pangasinán. From not being given a place in public instruction the writing of our language has fallen into such a state of disorder and confusion that it has become a source of real embarrassment to every intelligent native of our province. To remedy the evil, proposals of reform and standardization have at different times been made by our vernacular writers, most notable among whom has been Mr. Pablo Mejia of Dagupan with his chapter on orthographic rules (“Piga’ran pananuntonan ed panunulat”) added to his work “Bilay tan kalkalar nen Rizal”) (The life and examples of Rizal, Manila 1923). When considering the different systems used in writing our language, and the proposals for their unification, it appeared to me that prior to a discussion of letters that have their existence only on paper, a discussion might profitably be had of the sounds of which such letters should, after all, be but the symbols. For much as our orthographic alphabet, to be acceptable to the general public, will have to submit to certain conventionalities, it should not be established in complete disregard of our phonetic alphabet, that is, of the sounds with which the living language speaks and endears itself to us. To what extremes it will lead if the written words of a language are allowed to cease being consonant with the spoken words is shown by English with its frequent divergency of spelling and pronouncing. It was from this consideration that I undertook before all the study of the Pangasinán sound-system, the results of which I here present in scientific arrangement and with such explanations as appeared to me necessary or convenient.